Research-Based Learning and Digital Literacy: A Mediation Analysis of Academic Motivation on Student Research Competencies - Sri Mulyati; Iskandar Iskandar; Atin Nuryatin; Yeyen Suryani; Nur Umamah (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2025)
Research skills are a crucial competency in higher education, yet a notable gap often exists between curriculum requirements and students’ practical application abilities. This study aims to identify factors influencing students' research skills, specifically analyzing the role of research-based learning (RBL) and digital literacy in skill improvement. Furthermore, the study explores the mediating role of academic motivation in the relationship between RBL, digital literacy, and research skills. This study employed an explanatory survey method with a quantitative approach. Data were collected via a questionnaire distributed to 289 students from the Faculty of Teacher Training and Education, Kuningan University, during the 2024/2025 academic year. The instrument utilized was a structured questionnaire based on a measurement scale. Data analysis utilized mediation regression with SEM-PLS to test the relationships and influence between variables. The results indicated that RBL and digital literacy significantly and positively contributed directly to the enhancement of students' research skills. Furthermore, academic motivation was found to play a positive role as a mediating variable, increasing the influence of RBL and digital literacy on students' research skills. These findings offer practical implications for universities to strengthen RBL implementation (through research assignments and collaborative projects) and enhance digital literacy (through training on accessing sources and data analysis software). Additionally, higher education institutions are advised to foster a learning environment supporting academic motivation through recognition and constructive feedback. Future research may expand the variables by incorporating factors such as faculty support or academic culture for a more comprehensive understanding.Keywords: research skills; research-based learning; digital literacy; academic, motivation